Transformasi Ilahi di Tengah Dekadensi Moral: Tafsir Pentakostal atas 1 Korintus 6:11 - Sitanggang, Vernineto (Sekolah Tinggi Teologi Berita Hidup, 2025)
This article presents an in-depth analysis of 1 Corinthians 6:11, departing from the historical context of the first century Corinthians who experienced moral decadence in line with the reality in today's Indonesia where Christians fail to show behavior that has undergone divine transformation. This verse serves as a rhetorical and theological climax in Paul's argument against sinful practices in the church. Through a theological analysis from the Pentecostal perspective of three key terms: washed, sanctified, and justified by God's central role, it is shown that the verse is not merely a warning, but rather a proclamation of a fundamental new identity for believers as a divine transformation in the midst of moral decadence. It is concluded that 1 Corinthians 6:11 is a transformative divine declaration, transforming the identity of sinners into heirs of God's Kingdom that has been washed, sanctified, and justified. In the Pentecostal perspective, the work of the Holy Spirit is the foundation for divine transformation.